Dysmenorrhea and Its Effects on School Absenteeism and School Activities among Adolescents in Selected Secondary Schools in Ibadan, Nigeria - Femi-Agboola, Damilola M. (Niger Med J, 2017)
BACKGROUND: Menstruation can be associated with dysmenorrhea that may affect daily activities. This study aimed to determine the prevalence of dysmenorrhea, effects on school activities, and associated school absenteeism among secondary school girls in Ibadan, Nigeria. MATERIALS AND METHODS: This cross-sectional study was among 460 students from all girls' only secondary schools in Ibadan, Nigeria, using a cluster sampling method. Data were collected using questionnaires and focus group discussions. The severity of dysmenorrhea was categorized as mild, moderate, and severe. Data collected were analyzed using descriptive statistics and Chi-square tests performed to determine significant associations. Level of statistical significance was set at 5%. RESULTS: Prevalence of dysmenorrhea and school absenteeism was 73% and 13.1%, with the severity of dysmenorrhea being 37.5%, 43.8%, and 18.8% for mild, moderate, and severe dysmenorrhea. Other school activities affected were as follows: class concentration, class participation, social, and sports activities (17.6%, 12.2%, 10.9%, and 4.6%). Main sources of medication for pain relief were family (15.8%) and self (13.7%). Age and duration of menstruation predicted dysmenorrhea (odds ratio [OR] =3.5, confidence interval [CI] = 1.2–9.7, P = 0.019), (OR = 1.7, CI = 1.1–2.6, P = 0.022), whereas severe dysmenorrhea predicted school absenteeism (OR = 4.2, CI = 1.7–9.9, P = 0.001). Respondents opined that analgesic drugs should be available in school to prevent school absenteeism. CONCLUSION: Prevalence of dysmenorrhea was high and severe dysmenorrhea played a role in school absenteeism. Health education should be provided to address the dangers of self-medication while drugs for pain relief should be available in schools.